Potential gains from water rights trading in the Aral Sea Basin - Bekchanov, Maksud; Bhaduri, Anik; Ringler, Claudia (Elsevier, 2015)
Increasing water demand due to population growth, irrigation expansion, industrial development, and the need for ecosystem improvement under mounting investment costs for developing new water sources calls for the efficient, equitable and sustainable management of water resources. This is particularly essential in the Aral Sea Basin (ASB) where ineffective water management institutions are the primary reason of intersectoral and inter-state water sharing conflicts and lack of incentives for improving water use efficiency. This study examined market-based water allocation as an alternative option to the traditional administrative allocation to deal with water scarcity issues in the ASB. Potential economic gains of tradable water use rights were analyzed based on a newly constructed integrated hydro-economic river basin management model. The analysis differentiates between inter-catchment and intra-catchment water rights trading. The results show that compared to a baseline with fixed water use rights, inter-catchment water rights trading can increase basin-wide benefits by US$ 373–476 million. Under intra-catchment trading, gains are still US$ 259–339 million, depending on relative water availability. Gains from trade are larger under drier conditions. However, water rights trading carries a series of transaction costs. We find that in case transaction costs exceed US$ 0.05/m3 of water traded there is no additional economic gain from water rights trading. Enforcement of the rule of law, infrastructural improvements, participation of representatives of key water stakeholders in decision making processes, and mutual trust and cooperative relationships among the riparian countries are suggested as means for reducing transaction costs of water rights trading contracts.